Image Stego Detection using Higher Order Statistics - Yousif, Ammar Moufak J.; AL-a'zawi, Mahir K. (Nahrain University College of Engineering Journal, 2010)
The basic approach taken here works by finding predictable higher-order statistics of natural images within a multi-scale decomposition, and then showing that embedded messages alter these statistics. A Fisher linear discriminant analysis is then used to discriminate between untouched and adulterated images. Detection system suggested here is used to detect seven systems these are: hiding in LSB, hiding in palette, hiding in DCT simple level security, and hiding in wavelet simple level security. In addition, highly-secret systems were constructed, i.e. systems that integrate Cryptography with Steganography in both domains, DCT and Wavelet. Moreover, system of hiding in multiwavelet was used with cryptography.